Analisis Inovasi Media Pembelajaran Pendidikan Agama Islam Berbasis ICT di Pondok Pesantren Nurul Haramain Narmada Lombok Barat - Muhajirin Ramzi; M. Arzani; Hamidi Hamidi; Junaidi Junaidi (CV. Creative Tugu Pena, 2025)
This study aims to analyze institutional policies, technological infrastructure, and the implementation of Information and Communication Technology (ICT)-based learning media in Islamic Religious Education (PAI) at Nurul Haramain Islamic Boarding School, Narmada, West Lombok. A qualitative descriptive approach with a case study design was employed. Data were collected through in-depth interviews with school leaders, digital transformation coordinators, and PAI teachers, complemented by observations and document analysis. The data were analyzed using an interactive model involving data condensation, data display, and conclusion drawing and verification, while data trustworthiness was ensured through source and methodological triangulation. The findings reveal that ICT-based learning innovation is supported by strong institutional leadership, the TUGU SASAK program, Computerized-Based Classes, computer laboratories, multimedia classrooms, a digital library, a data center, and internet connectivity. ICT-based learning media are implemented through digital presentations, instructional videos, audiovisual learning materials, computer-based assessments, and online learning resources across Fiqh, Qur'an-Hadith, Aqidah-Akhlaq, and Islamic Cultural History subjects. These practices enhance student engagement, expand access to learning resources, improve instructional efficiency, and strengthen conceptual understanding. However, challenges remain, including disparities in teachers' digital competencies, limited technological resources, and the need for stronger pedagogical design and digital ethics. The study contributes to the literature by proposing an integrative framework that connects institutional leadership and policy, technological ecosystem readiness, ICT-supported PAI pedagogy, and the internalization of Islamic values as interconnected dimensions of digital transformation in pesantren. The findings further suggest the importance of continuous teacher professional development, equitable infrastructure governance, and context-sensitive technology policies to support sustainable digital transformation in Islamic education.